Analysis of Risk and the Hazardous Chemical Waste Management System at Sembiring Regional General Hospital Delitua - Herlina Herlina (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Hospitals generate hazardous chemical waste (B3) that may harm human health and the environment if improperly managed. Objective: This study aims to analyze the waste management system and risk associated with B3 waste at RSU Sembiring Delitua. Research Methods: A descriptive analytic study using a mixed-methods approach was conducted. Data were collected through observation, in-depth interviews, KAP questionnaires (Knowledge, Attitude, Practice), and document analysis. Risk assessment was performed using the Hazard Identification and Risk Assessment (HIRA) method. Results: While the waste management system covers basic procedures, weaknesses were identified in waste segregation, inadequate storage facilities, and insufficient personal protective equipment use. The highest risk was found in the storage process (risk score 12, very high category). Conclusion: Gaps remain between knowledge, attitudes, and practices in chemical waste management. Continuous training, improved facilities, and a strengthened safety culture based on risk management are necessary to enhance hazardous waste management systems in hospitals.